2003
DOI: 10.1258/095646203765371312
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of opportunistic infections in hospitalized HIV-infected patients in Phnom Penh, Cambodia

Abstract: The aim of the study was to provide more comprehensive data on the clinical characteristics of hospitalized AIDS patients in Cambodia. Chart review of 381 HIV-infected patients admitted to a public hospital in Phnom Penh, Cambodia between December 1999 and May 2000 was performed. The in-hospital mortality rate was 43.6%. Approximately 50% of patients had two or more concurrent illnesses. Very advanced HIV disease was common, with CD4 cell counts below 10 cells/mm(3) in 43.2%. Only 28.3% of the patients had doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 2 publications
4
21
0
1
Order By: Relevance
“…The spectrum of opportunistic infections in our patients is similar to those reported from South Africa [17], India [18], Cambodia [8] and Iran [19]. Tuberculosis was the most common inpatient diagnosis.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The spectrum of opportunistic infections in our patients is similar to those reported from South Africa [17], India [18], Cambodia [8] and Iran [19]. Tuberculosis was the most common inpatient diagnosis.…”
Section: Discussionsupporting
confidence: 85%
“…Opportunistic infections are a major cause of morbidity and mortality in patients with HIV infection. In resource-limited settings, knowledge regarding the prevalence of the various IOs might aid [2,[7][8][9]. This mortality rate is much higher than that reported in the United States in the pre-HAART era [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…In 2000, it was estimated that HIV prevalence among persons 15-49 years of age was nearly 3%, the highest among Southeast Asian countries [92,93]. A chart review of 351 patients with HIV admitted to the hospital for various reasons showed that 8% had PCP [93]. A later study of 100 patients with advanced HIV disease showed that noninduced sputum from 10% of patients contained Pneumocystis organisms [94].…”
Section: Asiamentioning
confidence: 99%
“…CM has been associated with approximately 15% of HIV-related hospital admissions in several studies [7,40,41] and is a leading cause of death in this population, with acute mortality rates ranging from 17% to 43% [4,42]. CM is also a commonly reported opportunistic infection in other areas of the world, including Latin America and India [43,44].…”
Section: Epidemiologymentioning
confidence: 99%